Cattle colonialism an environmental history of the conquest of California and Hawai'i - Fischer, John Ryan (The University of North Carolina Press, 2015)
"Environmental historians have too often overlooked California and Hawai'i, despite the roles the regions played in the colonial ranching frontiers of the Pacific World. In Cattle Colonialism, John Ryan Fischer significantly enlarges the scope of the American West by examining the trans-Pacific transformations these animals wrought on local landscapes and native economies" --
Includes bibliographical references and index. - "Portions of the text were previously published in John Ryan Fischer, Cattle in Hawai'i: biological and cultural exchange, Pacific historical review 76 (August 2007): 347-72"
Keywords: Geschichte; Umwelt; Wirtschaft; Ranching / Environmental aspects / History / California; Ranching / Environmental aspects / History / Hawaii; Ranching / Economic aspects / History / California; Ranching / Economic aspects / History / Hawaii; Viehwirtschaft; Nutztierhaltung; Umweltbelastung; California / Environmental conditions / History; Hawaii / Environmental conditions / History; California / Economic conditions / History; Hawaii / Economic conditions / History; Hawaii; Kalifornien